(untitled) (Asian Journal of Agriculture, 2022)
Abstract. Roy K, Khan AA, Rubayet MT, Haque MM. 2022. Production of quality seeds of chili using soil amendments. Asian J Agric 6: 7-14. The present investigation was conducted to produce quality chili seeds using soil amendments. The soil was amended with vermicompost, colonized Trichoderma, mustard oil cake, cow dung, and poultry manure for quality seed production. The fruit yield (3.63 t ha-1) and seed yield (2.40 t ha-1) were higher from colonized Trichoderma amended plot. All the organic amendments, such as colonized Trichoderma, vermicompost, poultry manure, mustard oil cake, and cow dung, increased the yield of chili seeds compared to the control. Quality characteristics of harvested seeds, such as germination, vigor, and 1,000 seed weight, were found higher in colonized Trichoderma amendment plots. Five fungi, namely Aspergillus sp., Fusarium sp., Colletotrichum capsici (Syd. & P.Syd.) E.J.Butler & Bisby, Curvularia sp., and Alternaria alternata (Fr.) Keissl. were found to be associated with seeds, and the infection rate of different fungi varied from 1.70 to 9.20%. The lowest (9.80%) total seed-borne infection was also recorded in seeds of colonized Trichoderma amended plot. The highest (3.73) benefit-cost ratio was obtained from colonized Trichoderma, followed by poultry manure (3.39) and vermicompost (3.33) amendment. Thus, soil amendment with colonized Trichoderma, vermicompost, or poultry manure is suggested to produce quality chili seeds with a higher yield.